The charming physician (El médico encantador): neurological conditions in a short story by Silvina Ocampo - Delgado García, Guillermo Rubén; Rodríguez Návarez, Carolina; Estañol, Bruno (2017)
ABSTRACT The Argentinian author Silvina Ocampo (1903-1993) left us a vast body of works which are considered outstanding in many ways. In 1960, she published a short story, entitled “El médico encantador” (The Charming Physician), in the renowned literary magazine Sur. The central character of this piece is a family doctor named Albino Morgan, who had a secret truth: in any house he visited, all variety of disease also entered. He brought with him the viruses he disseminated. The narrator of this short story—one of his patients—describes four of Morgan’s diseases. These imaginary neurological conditions allowed Ocampo to explore improbable situations in everyday life. Keywords: neurology; medicine in literature; medicine in art; agnosia; sleep initiation and maintenance disorders RESUMO A autora argentina Silvina Ocampo (1903-1993) deixou-nos uma vasta obra que é considerada excelente de várias maneiras. Em 1960, publicou um conto, intitulado “El médico encantador” (O médico encantador), na famosa revista literária Sur. O personagem principal desta obra é um médico de família chamado Albino Morgan que possuía uma verdade secreta: em qualquer casa que ele visitava, também entrava toda a diversidade de doenças. O narrador deste conto -um dos seus pacientes- descreve quatro das doenças de Morgan. Estas condições neurológicas imaginárias permitiu a Ocampo explorar as situações improváveis da vida quotidiana. Palabras-Clave: neurologia; medicina na literatura; medicina na arte; agnosia; distúrbios do início e da manutenção do sono.